Electrochemical oxidative regio- and stereo-selective thio(seleno)cyanation of enamides and mechanistic insights. Issue 17 (12th August 2022) - Gu, Qingyun; Cheng, Zhenfeng; Xiong, Xing; Xiong, Biao; Zhao, Yu; Xu, Hua-Dong; Zhang, Yanan; Qiu, Xiaodong; Zeng, Xiaobao
Abstract : An electrochemical oxidative thio(seleno)cyanation of enamides to synthesize various ( E )-β-thio(seleno)cyanated enamide compounds is reported herein. Abstract : An electrochemical oxidative regio- and stereo-selective thio(seleno)cyanation of enamides has been developed to access ( E )-β-thio(seleno)cyanated enamide compounds under environmentally-benign conditions without metal and exogenous oxidant in an undivided cell. The protocol features good reaction efficiency and functional group tolerance, providing a sustainable pathway for the thio(seleno)cyanation of enamides. The practicabilities of this protocol were further demonstrated by intramolecular cross-coupling reactions to prepare six- and seven-membered heterocycles by varying the position of halide substituents. Mechanistic investigation reveals that the reaction may proceed via [1, 5]-H sigmatropic rearrangement to achieve exclusive E stereoselectivity.